KLASIFIKASI ULASAN PELANGGAN SHOPEE MALL TERHADAP E-COMMERCE PENJUALAN BAJU BATIK METODE NAÏVE BAYES - Fahtu Rahman, M. Ade; Mair, Zaid Romegar; Sartika, Dewi (Universitas Budi Luhur, 2024)
Batik, as a symbol of Indonesian culture, has become an everyday lifestyle and is not only limited to ceremonial occasions. In the era of globalization, the advancement of batik making has integrated its presence in various aspects of life, including in casual and informal clothing choices. E-commerce, such as Shopee Mall, provides a means for consumers to purchase batik without leaving the comfort of their homes or workplaces. Nonetheless, online shopping carries higher risks and uncertainties, emphasizing the importance of building consumer trust. Customer reviews, as a valuable source of information, are key in helping consumers make purchasing decisions. This research applies the Naïve Bayes method to classify customer reviews related to batik clothes from five sellers at Shopee Mall. Based on the results of the research and discussion carried out, it is concluded that in classifying customer reviews regarding the sale of batik clothes, using the Naive Bayes method on data from 5 sellers, where each seller has 350 reviews from Shopee Mall, the highest accuracy value is achieved by the seller Batik Prakasa, with an accuracy value of 81.90%, precision 81.90%, and recall 100%. Meanwhile, the most positive words were achieved by Batik Kanaya 1 seller, with a total of 520 positive words and 156 negative words, and achieved an accuracy of 77.19%, precision of 77.19%, and recall of 100%.